On the role of tip curvature on flapping plates. (9th January 2018) - Martin, Nathan; Gharib, Morteza
Abstract: During the flapping motion of a fish's tail, the caudal fin exhibits antero-posterior bending and dorso-ventral bending, the latter of which is referred to as chord-wise bending herein. The impact of chord-wise tip curvature on the hydrodynamic forces for flapping plates is investigated to explore potential mechanisms to improve the maneuverability or the performance of autonomous underwater vehicles. First, actuated chord-wise tip curvature is explored. Comparison of rigid curved geometries to a rigid flat plate as a baseline suggests that an increased curvature decreases the generated forces. An actuated plate with a dynamic tip curvature is created to illustrate a modulation of this decrease in forces. Second, the impact of curvature is isolated using curved plates with an identical planform area. Comparison of rigid curved geometries as a baseline corroborates the result that an increased curvature decreases the generated forces, with the exception that presenting a concave geometry into the flow increases the thrust and the efficiency. A passively-actuated plate is designed to capitalize on this effect by presenting a concave geometry into the flow throughout the cycle. The dynamically and passively actuated plates show potential to improve the maneuverability and the efficiency of autonomous underwater vehicles, respectively.